El control interno y la eficiencia de la recaudación del impuesto predial del Gad Municipal de Machala - Yupangui Asanza, Mariuxi Viviana (2023)
Tax collection has been an important part of the budgets of the Decentralized Autonomous Governments (GAD in Spanish), therefore it is essential to know the role that this type of organizations have for the safeguard of the processes of collection and use of taxes. Therefore, this research sought to answer the question: What is the relationship between the internal control system and the efficiency of the property tax collection process, through the case study of the Machala Municipal Government? This question allowed discovering the hypothesis of whether there is a relationship between the variables: internal control and the efficiency of property tax collection in this GAD. For this purpose, quantitative research was carried out, in which two questionnaires were applied to workers of the institution, as well as to taxpayers of the same. Among the main findings, it was found that there are flaws in the internal control processes, as well as insufficient information on how taxes are used by taxpayers. A medium level of intensity was found in the correlation between the two main study variables: internal control and efficiency in property tax collection in the Machala Municipal Government.